O conhecimento, a atitude e o comportamento de empreendedores sergipanos na gestão das suas finanças pessoais e empresariais - Mota, Emanuela Rocha (2023)
As an alternative for people to achieve financial awareness, studies on the importance of Financial Literacy address that access to financial knowledge tends to provide individuals with the development of attitudes and behaviors that help them make decisions and draw up plans for improving quality of your life. Among the institutions that offer courses and/or workshops that guide entrepreneurs to understand how to manage their personal and professional finances, there is SEBRAE/SE Brazilian Support Service for Micro and Small Companies of Sergipe , an institution specialized in promoting the economic and sustainable development of entrepreneurs. Given this approach, the present work aims to analyze the perception of Sergipe entrepreneurs from micro and small companies about financial literacy for managing their personal and business finances, based on the contents and guidelines learned in courses/workshops on management financial. Through accessibility, five Sergipe entrepreneurs from micro and small companies assisted by SEBRAE were selected and interviewed. When deciding on qualitative research, life history, directive interview and nonparticipant observation were used as methods/instruments for collecting reports. In the analysis of the results, it was identified that the interviewees understood the need to seek financial knowledge to develop the management of their personal and business finances. They use not only SEBRAE/SE as a source of knowledge, but also access other options chosen according to their ease of understanding, such as books, lectures, guidance from family members or close people and/or videos available on social networks. And, as a result, it was found that financial literacy can be considered as a support for micro and small business entrepreneurs to manage their personal and professional finances. However, the willingness to want to change, driven by the gratitude perceived in the face of the rewards acquired, is the premise for the entrepreneur to seek financial knowledge as a stimulus to develop attitudes and behaviors that provide the improvement of their personal and business quality of life.